2020
DOI: 10.1007/s00773-020-00726-5
|View full text |Cite
|
Sign up to set email alerts
|

Unburned hydrocarbon formation in a natural gas engine under sea wave load conditions

Abstract: Although natural gas is documented as a low-emission fuel compared to the other traditional fossil fuels in internal combustion engines, recent research indicates large amounts of methane emission released by lean burn gas engines and highlights the importance of this emission on global warming. This paper aims at illustrating the main sources of unburned fuel in internal combustion engines with an emphasis on spark ignited natural gas engines. In addition, two unburned hydrocarbon modeling patterns, empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The engine speed operated around the constant value by adjusting the fuel rack position with a PID controller. The measured data and simulation results confirmed that the engine had satisfying stability around the speed setpoint [17]. The results of this section are divided into two groups: Performance output and emission formation.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The engine speed operated around the constant value by adjusting the fuel rack position with a PID controller. The measured data and simulation results confirmed that the engine had satisfying stability around the speed setpoint [17]. The results of this section are divided into two groups: Performance output and emission formation.…”
Section: Resultsmentioning
confidence: 52%
“…12 displayed the variation of unburned hydrocarbon in these two operational modes, with and without throttle. These authors' previous work [17] revealed that the UHC compound directly correlates with the air-fuel ratio, and a higher amount of excess air ratio deteriorated the combustion quality and resulted in the flame quench. Besides, flame quench was one of the three primary UHC sources in lean-burn spark-ignition gas engines together with gas exchange and crevice volume.…”
Section: Resultsmentioning
confidence: 96%
“…The majority of current studies focus on thermal efficiency and methane slip problems in steady states [81]. In sea conditions, time-varying loads have to be considered due to the fact that a decrease in the energy efficiency has been obtained at the part loads of gas engines [82], and the increase in emissions has been observed when gas engines work at wave load conditions [83,84]. To further reduce the emissions from gas engines, especially the methane slip, several methods have been proposed and examined [85][86][87].…”
Section: Advanced Methods To Enhance Transient Performancementioning
confidence: 99%